Cognitive styles: speed–accuracy trade-offs underlie individual differences in archerfish. (February 2020) - Jones, Nick A.R.; Webster, Mike; Newport, Cait; Templeton, Christopher N.; Schuster, Stefan; Rendell, Luke
Abstract : Individuals exhibit consistent differences in behaviour and related cognitive performance. 'Cognitive styles'-based hypotheses suggest the trade-off between speed and accuracy is an important factor where an individual's behavioural traits and linked decision speeds may account for its cognitive performance. The expected relationship between accuracy and decision speed, however, is not always clear and some studies have suggested that faster individuals do not suffer the expected cost to accuracy. Contradictory findings may be attributed to taxon-specific differences but may also be due to the difficulty in separating intraindividual from interindividual variation or the use of insufficiently challenging tasks in tests. We trained archerfish, Toxotes chatareus, to shoot at artificial targets for food, and then conducted a visual discrimination study to test the cognitive styles hypothesis. To reduce potential confounding effects, we used a longitudinal design, and increased the challenge of the test by using differentially rewarded targets. We also tested fish in one of two conditions with either two or three targets in each test. As expected, archerfish showed repeatable differences in latency to shoot and consistently fast individuals were quicker to achieve initial learning criteria than slower individuals. Repeated tests revealed an inverse relationship between discrimination accuracy and speed, with slower individuals having greater accuracy in initial trials on each day, supporting the cognitive styles hypothesis. However, this relationship was statistically significant only in the three-target condition, underscoring how task design can strongly affect the ability of researchers to detect robust individual variation in cognition. Taken together, our results support the hypothesis that speed–accuracy trade-offs can underlie some observed interindividual differences in cognition. Highlights: We report evidence to support the cognitive styles hypothesis in archerfish. Consistently fast fish learn to shoot novel targets quicker than slower fish. Consistently slower fish have greater discrimination success in three-choice tests. Even with differential rewards two-choice tests fail to reveal cognitive styles.